A Change Management View on Technology Adoption in Hotel Organizations: A Review and a Conceptual Framework - Francis Albert R. Somera; Krassie Petrova (Businesses)
In response to the rapid advancement in smart technology and the 2019–2020 pandemic, the hospitality industry has accelerated its adoption of innovative technologies. However, new technologies are often disruptive and may not be aligned with the organization’s strategy, technological expertise, and employee and customer expectations. This negatively affects the perceived value of the new technology and its adoption and continuous use. The review of the relevant research presented in this paper indicates that despite the many potential points of intersection between technology acceptance and adoption theories and studies of entrepreneurship and change management, these connections have not been explored in sufficient depth in the hospitality context. Drawing on extant theories, this study proposes a novel conceptual framework for the management of technology adoption in hotel organizations. The four stages of the framework represent the process of technology adoption from initiation to institutionalization to new challenges, connecting the theoretical constructs with the tangible needs of the hotel organizations. The framework considers technology adoption as a process of change that involves capability and leadership building. It shows how managing technology adoption through an integrated change management and digital capability-building perspective can lead to sustainable digital innovation. Practitioners can use the framework to systematically evaluate the potential of new and emerging technologies and develop the required digital competencies while managing organizational culture shifts and user resistance to change.